A nine-year (2012-2020) study of publication delay in an open access Library and Information Science journal - Majumdar, Sandip (Malaysian Journal of Library and Information Science, 2023)
This study attempts to map the publication delay of articles published in an international, peer-reviewed, open access Library and Information Science journal (LIS) i.e. the DESIDOC Journal of Library and Information Technology (DJLIT). An exploratory method was applied to collect data related to the editorial timeline through archival open access to the articles published in DJLIT during the period from 2012 to 2020. Data were tabulated in an Excel spreadsheet to facilitate statistical analysis and interpretation. The study finds a mean and median waiting time of approximately 176 days and 152 days respectively for articles before they got published. About 64.57 percent of articles went through revision. The majority of articles (i.e., 40.08%) experienced a delay between 100-199 days and were closely followed by 26.11 percent of articles with a delay of up to 99 days. Only 2.43 percent of articles fell in the 400-499 days delay category before being published. A strong influence of time between submission to final revision on overall publication delay was observed. The study did not find any correlation between the number of contributing authors and increasing delay in publication and contradicts the result obtained in another study on selected information science journals. The study is expected to help researchers and authors in the field of LIS to take informed decision before submitting their manuscripts to DJLIT for publication.